Building Digital Competency through Technology Adoption Support and Skills Development: The Mediating Role of Learning Agility - Salsabila Anissa Putri; Muhammad Sapruwan (DPPM Universitas Pelita Bangsa, 2025)
This study examines the effect of Technology Adoption Support and Continuous Skill Development Programs on Digital Competency in manufacturing companies in Bekasi Regency, with Learning Agility as a mediating variable. In the context of rapid digital transformation, the development of digital competencies is very important to face the challenges of Industry 4.0. The purpose of this study is to understand the relationship between technology support and skills development programmes on employees' digital capabilities. The method used is quantitative, with sampling through questionnaire respondents from the manufacturing sector in the Bekasi Regency industrial area, to gain insight into employee digital skills readiness. The novelty of this research lies in addressing inconsistent findings from previous studies by demonstrating how learning agility functions as a crucial mediator that links continuous skill development and technology support with digital competency. Theoretically, the study contributes to human resource and digital transformation literature by clarifying the mechanism through which agility accelerates digital capability building in manufacturing contexts. Practically, the findings provide explicit implications for HR managers and policymakers, highlighting the need to design training and technology adoption programs that not only enhance technical skills but also foster employees’ adaptive learning capabilities, ensuring sustainable competitiveness in the Industry 4.0 era.